2009
DOI: 10.2139/ssrn.1027947
|View full text |Cite
|
Sign up to set email alerts
|

The Italian Chamber of Lords Sits on Listed Company Boards: An Empirical Analysis of Italian Listed Company Boards from 1998 to 2006

Abstract: The purpose of the present paper is to contribute to the literature on country interlocks by illustrating and analysing the interlocking directorships in the Italian listed companies from 1998 to 2006. We find that over the entire period a high percentage of the Italian listed companies are connected with each other through a very small minority of directors. Such group of interlocking (overwhelmingly male) directors shows a remarkable stability over time with very few entrants and very few exits mainly relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
2
9
0
1
Order By: Relevance
“…Similar effects of different regulations on networks were found by Drago et al (2009) which showed that the reforms of corporate governance in the period 1998-2007 had an impact on the networks considered. We also found a community structure in the Italian directorship network and in this case the result is consistent with Piccardi et al (2009).…”
supporting
confidence: 65%
“…Similar effects of different regulations on networks were found by Drago et al (2009) which showed that the reforms of corporate governance in the period 1998-2007 had an impact on the networks considered. We also found a community structure in the Italian directorship network and in this case the result is consistent with Piccardi et al (2009).…”
supporting
confidence: 65%
“…Good agency relationships between controlling families and banks make deviations from target leverage more negotiable, with little or no penalty. We argue that Italian family firms face lower agency costs of debt because of the tight links between controlling families and banks (Bianchi et al, 2001;Santella et al, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…Caprio and Croci (2008) measure the voting premium in Italy from 1974 to 2003 and find that it has decreased over time but remained relatively high: it was 57% in 1990, 65% in 1995, 37% in 2000, and 20% in 2003. Finally, we may indirectly infer that, in Italy, agency costs of debt may be lower in family-controlled firms than in non-family peers. Bianchi et al (2001) and Santella et al (2007), by analyzing the relevance of interlocking directorship in Italian listed firms, show a huge network of director interlocks. This network heavily involves directors of non-financial firms controlled by families that hold seats on the board of directors of banks and other financial institutions, and vice versa.…”
Section: Debt Financing In Family Firms: the Agency Theory Approach Amentioning
confidence: 99%
See 1 more Smart Citation
“…The Italian capitalism has been characterized by the presence of cross shareholdings, pyramidal groups and as well as ID. Santella et al (2009) and Drago et al (2015) provide evidence that Italian capitalism was characterized by the use of the cross-financial participation by the "industrial families". In both cases cross-financial participation was typically associated with a dense interlocking directorship structure.…”
Section: Corporate Governance Reformsmentioning
confidence: 99%